Odpowiedź :
Odpowiedź:
[tex]\begin{cases}0,2x-0,5y=1\\-\frac{1}{4}x+\frac{1}{2}y=-1\end{cases}\\\\\\+\begin{cases}0,2x-0,5y=1\\-0,25x+0,5y=-1\end{cases}\\------------\\-0,05x=0\ \ /:(-0,05)\\\\x=0\\\\\\0,2*0-0,5y=1\\\\0-0,5y=1\\\\-0,5y=1\ \ /:(-0,5)\\\\y=-2\\\\\\\begin{cases}x=0\\y=-2\end{cases}[/tex]
Odpowiedź:
[tex]\left \{ {{0,2x-0,5y=1} \atop {-\frac{1}{4}x+\frac{1}{2}y=-1}} \right.[/tex]
[tex]\left \{ {{0,2x-0,5y=1} \atop {-0,25x+0,5y=-1}} \right.[/tex]
-------------------
-0,05x=0/:(-0,05)
x=0
0,2*0-0,5y=1
-0,5y=1/:(-0,5)
y=1*(-2)
y=-2
(x,y)=(0,-2)
Szczegółowe wyjaśnienie: